Mengenal Masalah Oromotor pada Bayi Prematur - Melda Warliani; Nilla Mayasari; Ferius Soewito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Indonesia ranked 5th within the countries with highest premature infant rate, with numbers of premature delivery is 675.700. The number is equal with the born rate 15.5 per 100 delivery each year. In premature infants some problem can be found, including oral feeding. Oral feeding problems in infant is caused by immature organ system, such as cardiopulmonal, central nervous system, oral muscles, et cetera. Proper treatment will prevent further complications and assist infants on their optimal growth and development.